Pivoting to the Digital Era: State Library Victoria's Redevelopment. Issue 5 (3rd September 2021) - Wyatt, Danielle; Leorke, Dale; McQuire, Scott
ABSTRACT: In 2017, the State Library of Figure 1 Figure 2 Victoria commenced Vision 2020, an AU$88.1 million redevelopment that aims to transition the established 19th century Library into the digital era. Over four years, the Library's physical spaces, provision of services, organizational structure, and the way it is experienced by users were reimagined and reshaped. Like many other major public library developments internationally, State Library Victoria's redevelopment is a response to broader economic and cultural shifts shaping the public life of cities and citizens in a digital era. This article situates the redevelopment within this broader transformation. We draw upon interviews with professional staff and users in order to understand the contrasting ways digital technologies and a digital culture are impacting upon libraries and their publics.